2019
DOI: 10.1111/ijfs.14433
|View full text |Cite
|
Sign up to set email alerts
|

Clarifying effect of different fining agents on mulberry wine

Abstract: Fining experiments have been conducted on mulberry wine, in which five fining agents (bentonite, gelatin, casein, egg albumin and PVPP) were investigated. The effect of these agents on polyphenol content, colour intensity, antioxidant activity and aromatic profile has been determined. In general, all treatments improved the limpidity of the mulberry wines to some extent. The wine was mostly negatively affected by gelatin and led to the greatest reduction of phenol content (16.61%), colour intensity (32.26%) an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 34 publications
(38 reference statements)
0
3
0
Order By: Relevance
“…Studies have shown that ingesting a certain quantity of eggs per day can promote good health (Dimarco, Norris, Millar, Blesso, & Fernandez, 2017;Shin et al, 2017). Besides dietary consumption, egg ingredients are extensively used in the food industry for antibacterial, culinary, and functional properties (Ren et al, 2020;Silvetti, Morandi, Hintersteiner, & Brasca, 2017). Some nutraceutical and pharmaceutical agents also contain egg proteins (Christian, Selmer, Smirnova, & Kulozik, 2018).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have shown that ingesting a certain quantity of eggs per day can promote good health (Dimarco, Norris, Millar, Blesso, & Fernandez, 2017;Shin et al, 2017). Besides dietary consumption, egg ingredients are extensively used in the food industry for antibacterial, culinary, and functional properties (Ren et al, 2020;Silvetti, Morandi, Hintersteiner, & Brasca, 2017). Some nutraceutical and pharmaceutical agents also contain egg proteins (Christian, Selmer, Smirnova, & Kulozik, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…However, there are still high frequencies of egg‐induced allergic reactions due to accidental exposure to egg proteins even after the enforcement of labeling for food allergens (Blom et al., 2018). The main potential reasons that make eggs difficult to avoid are: (i) Egg is an omnipresent food ingredient as a raw material or auxiliary components (in pastry industry, cookies, sauces, mayonnaise, ice cream, and some fried foods) (Boyano‐Martínez, Pedrosa, Quirce, & García‐Ara, 2012); (ii) Some egg restriction diets are unproperly labeled where potential contamination risks, such as nonfood sources or cross‐contacts, are not considered, and the lacking of expert instructions makes the situation worse (Bégin et al., 2017); (iii) Eggs are used in cosmetic and pharmaceutical industries, and some vaccines are egg based (Lesnierowski & Stangierski, 2018; Tseng et al., 2019); (iv) Some egg proteins, such as lysozyme, are used in wine and beer industry for refining or due to their antibacterial properties (Ren et al., 2020; Silvetti et al., 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Due to their high protein content and other properties, consuming a certain number of eggs every day can benefit health ( 10 , 11 ). In addition to dietary consumption, egg components are also widely used in the food industry for their antimicrobial, cooking, and other functional properties ( 12 ). Some nutritional and medicinal preparations also contain egg protein ( 13 ).…”
Section: Relationship Between Egg Allergy and Food Allergymentioning
confidence: 99%
“…Также было получено, что бентонит уменьшает участие красного и синего цветов и увеличивает долю интенсивности желтого цвета при выдержке вин в течение более длительного периода времени. Обработка желатином оказала менее значительное влияние на интенсивность цвета: так, у молодого вина этот показатель снизился с 7,3 до 8,6 %, у вина 18-месячной выдержки -с 8,4 до 11,8 %, 42-месячной выдержки -16,1 % [3].…”
Section: Abstract: Bentonite Clay Enrichment Gelatin Fractional Compo...unclassified
“…Процесс адсорбции белка на поверхностях бентонита зависит от различных факторов, включая состав, концентрацию бентонита и белков, температуру, рН и др. [1][2][3]. При этом данных в отечественной научной литературе по изучению данного вопроса приводится крайне мало.…”
Section: Abstract: Bentonite Clay Enrichment Gelatin Fractional Compo...unclassified